2016
DOI: 10.1155/2016/7694385
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1 Regulates Cortical Inhibitory Neuron Dendrite and Synapse Growth through DISC1

Abstract: Cortical inhibitory neurons play crucial roles in regulating excitatory synaptic networks and cognitive function and aberrant development of these cells have been linked to neurodevelopmental disorders. The secreted neurotrophic factor Neuregulin-1 (NRG1) and its receptor ErbB4 are established regulators of inhibitory neuron connectivity, but the developmental signalling mechanisms regulating this process remain poorly understood. Here, we provide evidence that NRG1-ErbB4 signalling functions through the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…It has been shown that NRG1 can enhance neuron dendrite complexity, which could be blocked by a knockdown of DISC1 . Furthermore, DISC1 expression can be increased by NRG1 [24]. Consistent with the findings in NRG1 , its co-worker DISC1 also seems not to be manipulated by THC.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It has been shown that NRG1 can enhance neuron dendrite complexity, which could be blocked by a knockdown of DISC1 . Furthermore, DISC1 expression can be increased by NRG1 [24]. Consistent with the findings in NRG1 , its co-worker DISC1 also seems not to be manipulated by THC.…”
Section: Discussionsupporting
confidence: 60%
“…DISC1 is an intracellular protein which has been described as a cofactor in dendrite growth [24]. Although knowledge about its detailed function remains diffuse in some areas, DISC1 translocation has been proven in a Scottish family with a high number of schizophrenic individuals [25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Altered expression was also confirmed for genes encoding the historical candidate NRG1 26 and its receptor ERBB4 (Fig. 2e ), both of which have previously been linked functionally to DISC1 27 , 28 . Expression of 12 of 52 genes encoding synaptic proteins that are targeted by recurrent CNVs in schizophrenia 3 is also altered (hypergeometric probability p = 0.001, Supplementary Table 1a, b ).…”
Section: Resultsmentioning
confidence: 52%
“…A salient example of the added utility of using NODDI is demonstrated in Colgan et al, where a tau pathology murine model demonstrated significantly higher neurite density in neocortex than in wild-type controls, correlating with the degree of tau burden, in the absence of significant FA and MD findings 51 . As DISC1 serves to regulate the development of synaptic growth and the organization of trans-synaptic structures and functions, it would thus be predicted to impact neuroimaging measures of neurite density and orientation 44,45,5254 . As anticipated, our Disc1 svΔ2 model harbors decreased neurite density in numerous salient regions of the brain including the hippocampal formation, the basal ganglia, and the neocortex, consistent with previous studies of both dysmorphic and decreased dendritic density and arborization as seen in models of both Disc1 under- and overexpression 55,56 .…”
Section: Discussionmentioning
confidence: 99%